2016
DOI: 10.1080/13854046.2016.1159730
|View full text |Cite
|
Sign up to set email alerts
|

Validity testing and neuropsychology practice in the VA healthcare system: results from recent practitioner survey

Abstract: Base rate estimates for SPVT failure in VA disability exams are comparable to those in other medicolegal settings. However, failure in routine clinical exams is much higher in the VA than in other settings, possibly reflecting the hybrid nature of the VA's role in both healthcare and disability determination. Generally speaking, VA neuropsychologists use SPVTs frequently and eschew pejorative terms to describe their failure. Practitioners who require only one SPVT failure to establish response bias may overcla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(24 citation statements)
references
References 40 publications
3
21
0
Order By: Relevance
“…As of 2015, surveys indicate that neuropsychologists, on average, administer four to six PVTs in total (i.e., three to four embedded PVTs and one to two stand-alone PVTs in each evaluation; Martin, Schroeder, & Odland, 2015 ). Within Veterans Affairs health settings, neuropsychologists report using five to eight PVTs ( Hirst et al, 2017 ), and when performance validity is assessed, 89% of neuropsychologists employ at least two PVTs ( Young, Roper, & Arentsen, 2016 ). Surveys of experts in neuropsychological validity testing also indicate an average number of eight PVTs in forensic neuropsychological evaluations ( Schroeder, Martin, & Odland, 2016 ).…”
Section: Invalid Presentation On Examination (Criterion B)mentioning
confidence: 99%
“…As of 2015, surveys indicate that neuropsychologists, on average, administer four to six PVTs in total (i.e., three to four embedded PVTs and one to two stand-alone PVTs in each evaluation; Martin, Schroeder, & Odland, 2015 ). Within Veterans Affairs health settings, neuropsychologists report using five to eight PVTs ( Hirst et al, 2017 ), and when performance validity is assessed, 89% of neuropsychologists employ at least two PVTs ( Young, Roper, & Arentsen, 2016 ). Surveys of experts in neuropsychological validity testing also indicate an average number of eight PVTs in forensic neuropsychological evaluations ( Schroeder, Martin, & Odland, 2016 ).…”
Section: Invalid Presentation On Examination (Criterion B)mentioning
confidence: 99%
“…Veterans were included in the performance valid group (PVT-Pass) if they performed above cutoffs on all PVT indices. These measures have been widely used to detect poor performance validity in Veterans with TBI history (Flaherty, Spencer, Drag, Pangilinan, & Bieliauskas, 2015;Jak et al, 2015;Lippa, 2018, Whitney, Davis, Shepard, Bertram, & Adams, 2009Young et al, 2016) and have shown adequate sensitivity, specificity (false positive rates <10%), and positive predictive power (Denning, 2012(Denning, , 2014Fazio, Denning, & Denney, 2017;Haber & Fichtenberg, 2006;Kulas, Axelrod, & Rinaldi, 2014;Schwartz et al, 2016;Spencer et al, 2013;Tombaugh, 1997;Young, Sawyer, Roper, & Baughman, 2012). Furthermore, it has been recommended that failure of even one PVT should warrant consideration of performance invalidity, particularly for tests with adequate positive predictive power used in populations with relatively high base rates including individuals with remote history of mTBI (Denning, 2019;Inman & Berry, 2002;Iverson & Franzen, 1996;Lippa, 2018;Proto et al, 2014;Vickery et al, 2004).…”
Section: Performance Validity Testsmentioning
confidence: 99%
“…Neuropsychological evaluation is often recommended to patients with persistent PCS to aid in diagnostic clarification and provide treatment recommendations. However, failure to adequately engage in testing, as measured by performance validity tests (PVTs) occurs in 17-68% of clinical evaluations of Veterans (Armistead-Jehle, 2010;Jak et al, 2015;Lippa et al, 2014;Russo, 2012;Whitney, Shepard, Williams, Davis, & Adams, 2009), with the highest PVT failure rates among mTBI and PTSD referrals (Young, Roper, & Arentsen, 2016). PVT failure is associated with poor outcomes such as lower community reintegration (Lippa et al, 2014), increased healthcare utilization (Horner, VanKirk, Dismuke, Turner, & Muzzy, 2014), and higher financial burden on the healthcare system (Denning & Shura, 2019), as well as artificially reduced cognitive test scores (Grills & Armistead-Jehle, 2016) and elevated reporting of psychiatric symptoms (Jurick et al, 2016;Larrabee, 2003;Suchy, Chelune, Franchow, & Thorgusen, 2012).…”
mentioning
confidence: 99%
“…Women are more likely to seek mental health treatment in general [ 44 ] and social support (such as being married) is often a motivator to seek treatment [ 45 ]. Service connected disability has a complicated relationship with number of visits, as veterans may believe that they need to have documentation of continuing symptoms in order to retain or increase their disability rating [ 46 ]. Yet, service utilization often decreases after a veteran receives a desired level of disability [ 47 ].…”
Section: Discussionmentioning
confidence: 99%